Influence of Oyster Mushroom Waste on Growth Performance, Immunity and Intestinal Morphology Compared With Antibiotics in Broiler Chickens - Hassan, Reda A.; Shafi, Manal E.; Attia, Khalil M.; Assar, Mohamed H. (Frontiers in Veterinary Science, 2020)
Oyster mushroom waste (OMW) is a by-product of the agriculture industry with valuable antimicrobial, antioxidant, antifungal and prebiotic properties that may be a useful alternative to antibiotic growth stimulators in poultry nutrition. This experiment was conducted to examine the impact of OMW on the intestinal morphology and immune responses of broiler chickens. Four dietary therapies with 5 replicates of 15 birds in each, totalling 300 day- Ross 308 broiler chickens, were used in this experiment. Control chickens were fed a mixed diet that included a maize-soybean meal complemented by 1% and 2% OMW in addition to the basal diet. Furthermore, Enramycin [125 g/kg] was added to the control diet as an antibiotic. Throughout this experiment, performance was studied, as well as the immune response to the Newcastle Disease Virus [NDV] and intestinal morphological traits. A substantial surge was noted in body weight gain [BWG] and feed intake [FI] of chickens after the addition of 1% OMW [p ≤ 0.05]. In contrast, feed supplementation with 2% OMW, compared with the control diet, produced no noteworthy increase in BWG or the feed conversion rate [FCR]. In addition, total cholesterol decreased in the control group. Antibiotic addition, on the other hand, increased serum cholesterol [p ≤ 0.05]. After 42 days, neither OMW nor antibiotic addition affected organ mass. In contrast, antibiotic addition reduced the small intestine percentage, crypt depth and villus height [p ≤ 0.05]. The Newcastle disease vaccine [NDV] antibody titer improved after feed supplementation with 1% OMW in comparison with the control and antibiotic regimes. Furthermore, OMW supplementation decreased the heterophil-to-lymphocyte H/L ratio [p ≤ 0.05]. The use of OMW led to a reduction in the malondialdehyde [MDA] content of the breast and liver and an increase in glutathione peroxidase. It helped to reduce glutathione S-transferase, glutathione and glutathione reductase. The effects of OMW were dose-dependent. In conclusion, the use of 1% OMW in broiler diets enhanced their growth and immunity. Nonetheless, supplementation with 2% OMW produced conflicting results.